Immunity & Inflammation - Cao, Xuetao; Hoffmann, Jules; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Immunity & Inflammation aims to publish high-quality papers that explore groundbreaking discoveries and insights across the spectrum of immunity and inflammation, from basic science to translational and clinical research. The journal particularly welcomes studies that examine the dual role of inflammation$1 (Bhow appropriate inflammatory responses are essential for initiating and regulating normal immune functions, while dysregulated or excessive inflammation contributes to the pathogenesis of various inflammatory diseases. Topics include, but not limited to: Mediators and regulators in immunity and inflammation (cytokines, inflammasomes, sterile inflammation, immunoaging, neuroinflammation, and inflammation resolution) Immune responses in inflammatory diseases (tumor immunology, autoimmunity, allergies, mucosal immunology, and neuro-immunology) Cell therapy and immunotherapies (immune checkpoint blockade, cytokine therapies, anti-inflammatory drugs, and vaccines) Advanced technologies in immunity (omics, live-cell imaging, gene editing, and synthetic immunology) Through a focus on these areas, Immunity & Inflammation seeks to foster a deeper understanding of inflammation$1 (Bs role in immunity and promote innovative approaches to prevent and treat inflammation-related diseases. Submissions that delve into the kinetics and dynamics of inflammatory responses$1 (Bsuch as the temporal regulation of immune activation and inflammatory resolution, or the spatial interplay of cellular and molecular mediators within tissues$1 (Bare highly encouraged. The journal is also keen on research addressing inflammation-mediated diseases, conceptual breakthroughs in immune regulation, the development of novel anti-inflammatory drugs, and advances in immune-omics and technologies.s
Keywords: Immunology; Cancer; Inflammation; Immunotherapy; Immunology; Biotechnology; Immunology; Cancer Biology; Inflammation; Immunotherapy; Translational Immunology; Biotechnology